The Relationship Between Stress and Sleep Quality Among Undergraduate Students In The Applied Nursing Program At Poltekkes Kemenkes Palu - Lina Waldana; M. Noor Infansyah; Zubaidah (Salando Health Journal, 2026)
Background: Brand image plays an important role in influencing loyalty toward healthcare services. In the increasingly competitive healthcare sector, hospitals are required to build a positive image to maintain patient loyalty and improve service sustainability. This study aimed to analyze the relationship between brand image and patient loyalty at Hospital X. Methods: This study used a quantitative method with a cross-sectional design conducted at the outpatient unit of Hospital X in April 2026. A total of 100 respondents were selected using a purposive sampling technique. Data were collected through a closed-ended questionnaire using a Likert scale that had been tested for validity and reliability. Data were analyzed using univariate analysis to describe the distribution of respondent characteristics and variables, while bivariate analysis using the Spearman Rank correlation test was conducted to examine the relationship between variables. Results: The results showed that most respondents perceived the hospital’s brand image as good (91%) and had a high level of patient loyalty (81%). Statistical analysis revealed a significant relationship between brand image and patient loyalty, with a p-value of 0.001 and a correlation coefficient of 0.681, indicating a strong positive correlation. Conclusion: This study confirms a significant positive relationship between hospital brand image and patient loyalty. Patients who perceive a more positive brand image tend to demonstrate higher levels of loyalty. These findings highlight the importance of brand image as a factor associated with patient loyalty in hospitals